Neoadjuvant (chemo)radiotherapy and Lateral Node Dissection: Is It Mutually Exclusive? - Ogura, Atsushi; van Oostendorp, Stefan; Kusters, Miranda (Clinics in Colon and Rectal Surgery, 2020)
The importance of total mesorectal excision (TME) has been the global standard of care in patients with rectal cancer. However, there is no universal strategy for lateral lymph nodes (LLN). The treatment of the lateral compartment remains controversial and has gone to the opposite directions between Eastern and Western countries in the past decades. In the East, mainly Japan, surgeons consider LLN metastases as regional disease and have performed TME with lateral lymph node dissection (LLND) without neoadjuvant (chemo)radiotherapy ([C]RT) in patients with clinical Stage II/III rectal cancer below the peritoneal reflection. In the West, neoadjuvant radiotherapy or has been the standard, and surgeons do not perform LLND assuming the (C)RT can sterilize most lateral lymph node metastasis (LLNM). Recent evidences show that lateral nodes are the major cause of local recurrence after (C)RT plus TME, and LLND reduces local recurrence particularly from the lateral compartment. Probably a combination of the two strategies, that is, neoadjuvant (C)RT plus LLND, would be needed to improve outcomes in patients with lateral nodal disease.
Keywords: rectal cancer; lateral lymph node; lateral lymph node dissection; radiotherapy; chemoradiotherapy